Nutritional and Sensory Properties of Formulated Biscuits Supplemented with Vernonia amygdalina Del Leaves And Heteroclarias Spp Viscera Oil - Omolola Soji-Omoniwa; Omolade Bosede Olugbenga; Phoebe Adedamola Adewuyi; Olatunji Peter Ajao; Daniel Olasunkanmi Awe; Pelumi Zecharaiah Olawale; Khadijah Adedolapo Badmos; Jubril Akinpelumi Omotosho (Food ScienTech Journal, 2024)
The high prevalence of nutrition-related health issues has spurred a growing interest in developing healthier snack alternatives. The aim of this study therefore was to develop and assess the sensory as well as the nutritional properties of biscuits supplemented with Vernonia amygdalina leaf (VA) and Heteroclarias spp viscera oil.  Four biscuit samples were developed: one without Vernonia amygdalina and fish oil (labeled BWVF) and three others containing increasing quantities of VA (BWVF-1 g, BWVF-2 g, and BWVF-3 g). A commercially purchased conventional biscuit (CB) was utilized as a control. Physicochemical parameters of fish viscera oil, proximate analysis and sensory evaluation using a 9-point hedonic scale was carried out on the formulated biscuits. Results showed that the physicochemical properties of the fish viscera oil were within range recommended for edible oil. Carbohydrate was significantly lower (p < 0.05) in BWVF- 1 g, BWVF- 2 g and BWVF- 3 g in a dose dependent manner compared to the CB, while percentage crude protein, lipid and ash contents increased significantly (p < 0.05) compared to CB. The rating of appearance, texture/consistency, crunchiness, and overall acceptability of the test biscuits were not significantly different (p > 0.05) to CB. However, there was a dose-dependent decrease in the ratings for the taste of BWVF-1 g, BWVF-2 g and BWVF-3g compared to CB and BWVF. In conclusion, Vernonia amygdalina and fish oil-supplemented biscuits have good sensory evaluation and contain nutrients that can contribute to the daily nutritional and caloric needs of consumers.